Premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) in Indonesian women - Ova Emilia Ova Emilia Ova Emilia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Data from epidemiologic surveys showed that the burden of illness caused by premenstrual syndrome could not be underestimated. It has been estimated that the frequency of premenstrual symptoms was quite high (80-90%1, and in some women, the symptoms were so severe that they might interfere with daily activities. Most epidemiological studies of PMS were conducted in Western women, though a few small sample-size studies of Chinese and Japanese women indicated that they were affected by PMS. Objective: To find out the characteristic features of premenstrual symptoms in Indonesian women.Methods: Four hundred and sixty women aged between 20 and 49 yrs. with regular menstrual cycles, who were seen at a Women Health Clinic, were assessed regarding their premenstrual symptoms using the Premenstrual Symptoms Screening Tool (PSSTI. They were able to provide informed consent. The study was conducted in July 2007 until January 2008.Results: As many as 95% of these women were found to have at least premenstrual symptoms. The rates of prevalence of moderate to severe PMS and PMDD in this study were 3.9% and 1.1 %, respectively, which were lower than those in Western or Chinese and Japanese women. Only 5 women with moderate to severe PMS and PMDD were treated and 10.5% women seek herbal medicine to reduce premenstrual symptoms.Conclusion: Severe to moderate premenstrual symptoms and PMDD were suffered by 5% women and mostly affected 20-29 year old women. Medical treatment was rarely sought, but herbal medicine was often used to relieve premenstrual symptoms.Key words: PMS - PMDD - Indonesian women